Thematic Analysis of Clinician Documentation Surrounding Treatment Discussions and Decision‐Making in Patients With Desmoid Tumors - Victoria Wytiaz; Tianyi Wang; Scott Schuetze; Nina J. Francis‐Levin; Rashmi Chugh (Cancer Medicine)
ABSTRACT Background Desmoid tumors are benign tumors without metastatic potential. While progression is rarely life‐threatening, it is often life‐affecting with significant morbidity. The rarity of desmoid tumors and the inability to accurately predict their natural history lead to challenges in developing treatment algorithms or formulaic discussions to address treatment options with patients. Aims To better understand this process, we performed a qualitative study of clinician documentation for patients with desmoid tumors to identify themes and areas for improvement. Methods An institutional database search was used to identify patients with desmoid tumors seen from 2018 to 2023. Documentation entries in the electronic health record (EHR) were reviewed, and passages pertaining to treatment were abstracted and explored using inductive thematic analysis. Results Ninety‐five patients were identified. Generated themes included (1) balancing uncertainty and ambiguity with hope, (2) empowerment through patient‐initiated treatment discussions, (3) maintaining an active lifestyle and mitigating psychosocial distress, and (4) fostering longitudinal clinician–patient relationships and building trust. Conclusions The current analysis of documentation pertaining to treatment for patients with desmoid tumors provides insight into clinician–patient discussions and decisions in a real‐world clinical setting. The emergent themes provide novel guidance and support for optimizing treatment discussions and decisions. More robust community peer support groups specific to patients with desmoid tumors and clinician “support groups” may provide a way for both patients and clinicians practicing in a disease state with uncertainty to share experiences and improve resilience. Developing treatment educational materials for patients and families and improving access to supportive psychosocial services may further enhance high‐quality decision‐making.